2018
DOI: 10.1093/cid/ciy585
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Guidance 2018 Update: AASLD-IDSA Recommendations for Testing, Managing, and Treating Hepatitis C Virus Infection

Abstract: Recognizing the importance of timely guidance regarding the rapidly evolving field of hepatitis C management, the American Association for the Study of Liver Diseases (AASLD) and the Infectious Diseases Society of America (IDSA) developed a web-based process for the expeditious formulation and dissemination of evidence-based recommendations. Launched in 2014, the hepatitis C virus (HCV) guidance website undergoes periodic updates as necessitated by availability of new therapeutic agents and/or research data. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
262
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(270 citation statements)
references
References 109 publications
4
262
1
3
Order By: Relevance
“…In a recently issued report by the United States Food and Drug Administration (FDA), rare but serious liver injuries or failures were seen in patients with advanced liver disease who had received PI‐containing DAA therapy including GLE/PIB (Mavyret) and ELB/GRA (Zepatier). In decompensated liver disease, PIs are contradicted and have been highlighted by practice guidelines . High efficacy and safety of DAA therapy have broadly increased its uptake in patients with cirrhosis and/or HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently issued report by the United States Food and Drug Administration (FDA), rare but serious liver injuries or failures were seen in patients with advanced liver disease who had received PI‐containing DAA therapy including GLE/PIB (Mavyret) and ELB/GRA (Zepatier). In decompensated liver disease, PIs are contradicted and have been highlighted by practice guidelines . High efficacy and safety of DAA therapy have broadly increased its uptake in patients with cirrhosis and/or HCC.…”
Section: Discussionmentioning
confidence: 99%
“…During the era of interferon‐based therapy, treatment of HCV was limited in patients with cirrhosis due potential adverse events of therapy that were difficult to tolerate and often precipitated decompensation. The availability of DAAs with excellent safety profiles and higher efficacy now offer the prospect of treating this high‐risk patient group . Many studies revealed that viral clearance following DAAs has been associated with decline in liver stiffness and possible fibrosis regression; however, most of these studies were retrospective, including small number of patients and short follow‐up periods, and so definitive conclusion about the changes in hepatic fibrosis following DAAS therapy is not solid; also, most of these studies do not clearly differentiate between pre‐cirrhotic stage (F3) and established cirrhosis (F4).…”
Section: Introductionmentioning
confidence: 99%
“…The sustained virologic response (SVR) rate in cirrhotic patients is also not satisfactory, which can be as low as 38% [7]. Recently, the discovery of direct acting antiviral agent (DAA) regimens overturns the obstacles encountered in Peg-IFN/RBV regimen, leading to nearly 100% SVR rate and applicable regardless of cirrhotic status [8,9]. However, a recent meta-analysis concluded that the HCC occurrence and recurrence rates were comparable between DAA-and IFN-treated patients regardless of the higher SVR rate of the DAA regimen [10].…”
Section: Introductionmentioning
confidence: 99%